PENGARUH PENERAPAN GOOD GOVERNANCE, PENGENDALIAN INTERNAL DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KEUANGAN PEMERINTAH YANG DIMODERASI OLEH KOMITMEN ORGANISASI (Studi Pada Daerah Kabupaten Kampar) - Irayana, Ulya; Putri, Annie Mustika; Agustiawan, Agustiawan (Jurnal Daya Saing, 2024)
The purpose of this study is to assess the impact of good governance, internal control, and leadership style on financial performance, with organizational commitment acting as a moderator. The study will be conducted in Kampar Regency. This study uses a quantitative methodology, using a questionnaire as the main means of data collection. Data are measured on a Likert scale. Data are analyzed using the Structural Equation Modeling (SEM) method, using an alternative approach known as Partial Least Squares (PLS) through the use of the Smart-PLS 4.1.0.6 application. The findings of this study indicate that Good Governance has a substantial impact on Financial Performance, Internal Control has a substantial impact on Financial Performance, Leadership Style has no impact on Financial Performance, Organizational Commitment can moderate the relationship between Good Governance and Financial Performance, Organizational Commitment can moderate the relationship. Organizational Commitment has the ability to modify the relationship between Leadership Style and Financial Performance, in the context of Internal Control and Financial Performance.